REGULASI TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP ANAK - HIDAYAT, SARIP (Riau Law Journal, 2024)
AbstractChildren are the nect gereation who will realize the ideals of the indonesian nation in the furture. The future fate of Indonesia will be in the hands of children, so children’s growth and development needs ti be paid attention to. The phenomenon of sexsual violence againts chindren needs to receive great attention from parents, society and the government. The child protection law regulates various aspects of child protection, including protection against secual violance, children’s right and the obligations of parents, the state and society to protect childeren. Sexual violance children includes actions such as kissing or touching the child’s genitals, exposing the child’s genitals, or showing pornograpich materials or objects to the child. There are differences between Law no. 23 of 2002 and Law No. 35 of 2014 concering Amandments to Law ni. 23 of 2002 concering Child Protection, namely regarding criminals research metod. As in Decision Number 206/Pid.Sus./2021/PN. Ktb, the defendant has been legally and convincigly priven guilty of committing the crime of “ deceiving children to commit obscene acts”.